TAGAP restrains myeloid and T cell activation in inflammatory bowel disease - Lin, Rui-Ci; Shao, Zhifei (Frontiers in Immunology, 2025)
IntroductionInflammatory bowel disease (IBD) is characterized by chronic, relapsing inflammation of the gastrointestinal tract. Genetic factors, including variants in T-cell activation Rho GTPase-activating protein (TAGAP), contribute to disease susceptibility and severity.MethodsA newly identified TAGAP coding variant E147K was examined by GTP hydrolysis assay. To clarify the role of TAGAP in human immune regulation, CRISPR knockout approaches were employed to study functional changes of human myeloid and T cells. Murine studies, including anti-CD3 antibody injection and CD4+CD45RBhi T cell adoptive transfer models, were conducted to assess TAGAP-mediated Th17 responses and chronic colitis severity.ResultsIBD-risk-associated TAGAP variant E147K exhibited enhanced GTPase-activating activity. In human innate and adaptive immune cells, TAGAP restrained cell activation, migration, phagocytosis, and proinflammatory cytokine release. TAGAP deficiency led to significantly increased Th17 cell accumulation due to reduced apoptosis in the murine small intestine and exacerbated chronic intestinal inflammation.DiscussionThese findings demonstrated the role of TAGAP in immune responses and homeostasis. The E147K variant underscores TAGAP’s protective function in IBD, and further investigation is warranted to translate these insights into therapeutic strategies for autoimmune diseases.